Degraded collagenase deteriorates islet viability. - Brandhorst, H; Raemsch-Guenther, N; Raemsch, C; Friedrich, O; Kurfuerst, M; Korsgren, O; Brandhorst, D (2008)
OBJECTIVE: The utilization of purified enzyme blends consisting of collagenase class I (CI) and II (CII) and neutral protease is an essential step for clinical islet isolation. Previous studies suggested that the use of enzyme lots containing degraded CI reduced islet release from human pancreata. The present study sought to assess the effect of degraded collagenase on islet function in vitro and posttransplantation. MATERIALS AND METHODS: Crude collagenase was chromatographically separated into CI, CII, and a mixture of degraded CI and CII isomers. Subsequently, classes were recombined to obtain a CII/CI ratio of 0.5. Rat islets were isolated utilizing neutral protease and 20 units of recombined collagenase containing either intact (Ci) or degraded isomers (Cd). RESULTS: Digestion time was reduced utilizing Cd (P < .001). The highest islet yield and lowest islet fragmentation were obtained with Ci (P < .01). Utilization of Cd corresponded to a reduction in viability and in vitro function (NS). Islet transplantation reversed hyperglycemia in diabetic nude mice, but revealed an absence of weight gain in recipients receiving islets isolated using Cd (P < .01). CONCLUSION: This study suggested that islet function posttransplantation is affected by degraded collagenase isomers. This finding has to be considered for the purification process of collagenase.